2016
DOI: 10.1080/02626667.2014.992790
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity influences on stream water–groundwater interactions in a gravel-dominated floodplain

Abstract: Floodplains are composed of complex depositional patterns of ancient and recent stream sediments, and research is needed to address the manner in which coarse floodplain materials affect stream/groundwater exchange patterns. Efforts to understand the heterogeneity of aquifers have utilized numerous techniques typically focused on point-scale measurements; however, in highly heterogeneous settings, the ability to model heterogeneity is dependent on the data density and spatial distribution. The objective of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 38 publications
1
10
0
Order By: Relevance
“…[56][57][58]). It has been examined, among others, by [59][60][61]. Within the study area, the filled crevasses were masked with the sediments of subsequent floods, due to which some of them are poorly pronounced in valley bottom morphology.…”
Section: Discussionmentioning
confidence: 99%
“…[56][57][58]). It has been examined, among others, by [59][60][61]. Within the study area, the filled crevasses were masked with the sediments of subsequent floods, due to which some of them are poorly pronounced in valley bottom morphology.…”
Section: Discussionmentioning
confidence: 99%
“…Wildhaber et al (2014) found that fine sediment and streambed morphology also affected oxygen and water exchange. K rb also plays an important role in the dynamics of exchange fluxes and solute transport processes between the river and the surrounding GW system (e.g., Cardenas et al, 2004;Irvine et al, 2012;Kalbus et al, 2009;Käser et al, 2009;Lackey et al, 2015;Miller et al, 2016;Ryan & Boufadel, 2006;Song et al, 2007;Song et al, 2016;Woessner, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…The gravel was divided into three layers identified using electrical resistivity imaging data (Miller et al, 2014, 2016) from the location of the plot. The K s (m d −1 ) values for the gravel layers were determined using electrical resistivity data and the relationship below, which was developed using borehole permeameter data from the Barren Fork Creek site and one other floodplain site in the Ozark ecoregion (Miller et al, 2014, 2016): Knormals=0.11ρ where ρ is electrical resistivity (Ω m). The K s values for points within each gravel layer, as determined with electrical resistivity data, were then averaged to generate an average K s for that layer.…”
Section: Methodsmentioning
confidence: 99%